O GÊNERO INSTRUÇÃO DE USO ENQUANTO OBJETO DE ENSINO - Silva, Wagner Rodrigues (Intercâmbio, 2010)
Considering the necessity of developing a descriptive analysis of textual genres created by the National Program Parameters to the Portuguese Language teaching, this paper analyzes the text structure of the use instruction in labels.